Building Muslim-Buddhist understanding: the parallels of Taqwa/Allah consciousness in the Qur'an and satipatthana/mindfulness in Anapanasati Sutta - Yusuf, Imtiyaz (Oxford University Press, 2021)
Adopting a cross- cultural perspective on hierophanies, this chapter explores the fundamental structure of the religious experience of breath and breathing as expressed in Islamic and Buddhist traditions. 1 Copyright: not for sale or distribution Building Muslim–Buddhist Understanding 175 It seeks to describe the similarities between the concepts of taqwa (God consciousness, or consciousness of Allah in the Qur’an) and satipatthana (mindfulness in the Buddhist Anapanasati Sutta). It focuses on the relationship between life and consciousness as presented in the Qur’anic teaching that Allah breathed ruh into Adam (Qur’an 15:29), bestowing life and the ability to attain taqwa (Qur’an 2:2), and the Buddhist meditation of satipatthana, being conscious of the biological function of breathing in and out as means for liberation from Dukkha (suffering rooted in paticca samuppada, dependent origination). The chapter also examines comparisons between the Buddhist notion that life is characterized by suffering (Dukkha) and the Quranic notion that life is characterized by kabad (toil and struggle; (90:4)